Eggshell Pavilion: a reinforced concrete structure fabricated using robotically 3D printed formwork - Burger, Joris; Aejmelaeus-Lindström, Petrus; Gürel, Seyma; Niketić, Filip; Lloret-Fritschi, Ena; Flatt, Robert J.; Gramazio, Fabio; Kohler, Matthias (Construction Robotics (Online), 2023)
This paper discusses the design, fabrication, and assembly of the ‘Eggshell Pavilion’, a reinforced concrete structure fabricated using 3D printed thin shell formwork. Formworks for columns and slabs were printed from recycled plastic using a pellet extruder mounted to a robotic arm. The formworks were cast and demoulded, and the finished elements were assembled into a pavilion, showcasing the architectural potential of 3D printed formwork. The Eggshell Pavilion was designed and fabricated within the scope of a design studio at ETH Zurich. The structure was designed using a fully parametric design workflow that allowed for incorporating changes into the design until the fabrication. The pavilion consists of four columns and floor slabs. Each column and floor slab is reinforced with conventional reinforcing bars. Two different methods are used for casting the columns and floor slabs. The columns are cast using ‘Digital casting systems’, a method for the digitally controlled casting of fast-hardening concrete. Digital casting reduces the hydrostatic pressure exerted on the formwork to a minimum, thereby enabling the casting of tall structures with thin formwork. The floor slabs are cast with a commercially available concrete mix, as the pressure exerted on the formwork walls is lower than for the columns. In this research, 3D printed formwork is combined with traditional reinforcing, casting, and assembly methods, bringing the technology closer to an industrial application.